PENGEMBANGAN BAHAN AJAR DIGITAL MENGGUNAKAN FLIP BUILDER PADA MATERI NEGARAKU INDONESIA - Yulistiani, Sella; Kurnia, Dadang; Safitri, Nurlinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The lack of learning resources available in schools becomes less attractive still using printed teaching materials that only contain writing, so that students' interest in learning becomes less. The purpose of this study is to develop digital teaching materials using the flip builder application on the material Negaraku Indonesia grade IV SDN Ciawi 03 Bogor Regency. This type of research is Research and Development (R&D) development research with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Digital teaching materials using flip builder have been developed and tested through the validation of media experts with 94% of the reviews categorized as "very feasible", 100% of linguist validation declared "very feasible", and 91% of material experts with the category of "very feasible". As well as the student response questionnaire from 20 students received an average percentage of 92.6% with the category "very practical". Thus, it can be concluded that Digital Teaching Materials Using Flip Builder on My Country Indonesia Materials in Class IV SDN Ciawi 03 Bogor Regency have been declared very valid and very practical to use in learning.